Species Distribution, Antimicrobial Resistance, and Enterotoxigenicity of Non-aureus Staphylococci in Retail Chicken Meat - Soo In Lee; Sun Do Kim; Ji Heon Park; Soo-Jin Yang (MDPI AG, 2020)
Non-aureus staphylococci (NAS), including coagulase-negative staphylococci, have emerged as important causes of opportunistic infections in humans and animals and a potential cause of staphylococcal food poisoning. In this study, we investigated (i) the staphylococcal species profiles of NAS in in retail chicken meat, (ii) the phenotypic and genotypic factors associated with antimicrobial resistance in the NAS isolates, and (iii) the prevalence of classical and newer staphylococcal enterotoxin (SE) genes. A total of 58 NAS of nine different species were isolated from retail raw chicken meat samples. The occurrence of multidrug resistance in the NAS, particularly S. agnetis and S. chromogenes, with high resistance rates against tetracycline or fluoroquinolones were confirmed. The tetracycline resistance was associated with the presence of tet(L) in S. chromogenes and S. hyicus or tet(K) in S. saprophyticus. The occurrence of fluoroquinolone resistance in S. agnetis and S. chromogenes was usually associated with mutations in the quinolone resistance determining regions (QRDR) of gyrA and parC. In addition, the frequent presence of SE genes, especially seh, sej, and sep, was detected in S. agnetis and S. chromogenes. Our findings suggest that NAS in raw chicken meat can have potential roles as reservoirs for antimicrobial resistance and enterotoxin genes.